High speed society and the otherization of non-human animals - Pope, Annaliese (My University, 2025)
Within high-speed society individuals are confronted with an increasing amount of technologically mediated information, and sonic push notifications have reformulated our perception to be more attuned to our devices than to our non-technological surroundings (Berardi, 2009). Post-Fordist data mining has reshaped our perception so that, rather than empathically engage with non-human animal others, we continue to codify them as commodities due to our panicked overstimulation. By invoking Georg Simmel’s (1971a) blasé attitude, and the drive to highlight dissimilarities rather than that which is common, and Berardi’s (2015) shift to connective concatenations, I demonstrate that whereas the sounds of non-human animals may suggest a sameness with human animals, our shared phenomenological ‘fleshiness’ and, ideally, empathy, within a dystopic high speed society, such possibilities may be foreclosed through the codification of the (in)audible and a frenzied panic for survival (Abram, 2010).
Keywords: non-human animals; high-speed society; Georg Simmel; Franco "Bifo" Berardi; entangled empathy